Malaysia Moving Towards a Sustainability Municipal Waste Management - Tang, Yien Yu; Tang, Kuok Ho Daniel; Maharjan, Amit Kumar; Abdul Aziz, Azrina; Bunrith, Seng (Industrial and Domestic Waste Management, 2021)
The elevation of waste generation subsequent to population growth has become a severe environmental topic in Malaysia. Since most of the waste is being dumped into a landfill, the open dumpsite, or unsanitary landfills which are not constructed with proper engineering plan, severe impacts on the environment result. The energy demand in Malaysia increased with the growing population, but reliance on fossil fuels to generate electricity has created another greenhouse gas contributor. Alternatively, waste-to-energy technology solves the problem of increasing waste by converting the waste to a renewable energy source. Malaysia has moved towards landfill gas recovery system and incineration for waste energy recovery. The recovery system and refuse-derived fuel plant achieved expectation; however, the incineration plants have failed due to the opposition of the public, lack of funding and technician expertise, and other technical issues. The solid waste management practices lacking separation and recycling sources, become an obstacle for development. The government puts effort into solving the current issue by promoting recycling in the public, enforcing the legislation, and approaching new technologies for better solid waste management practice in the future. This paper aims to discuss the application of energy recovery from municipal solid waste in Malaysia.